Novel Computerized Health Risk Appraisal May Improve Longitudinal Health and Wellness in Primary Care - Nagykaldi, Z.J.; Voncken-Brewster, V.; Aspy, C.B.; Mold, J.W. (Applied Clinical Informatics, 2013)
Objectives: Health Risk Appraisals (HRAs) have been implemented in a variety of settings, however few studies have examined the impact of computerized HRAs systematically in primary care. The study aimed at the development and pilot testing of a novel, comprehensive HRA tool in primary care practices.Methods: We designed, implemented and pilot tested a novel, web-based HRA tool in four pair-matched intervention and control primary care practices (N = 200). Outcomes were measured before and 12 months after the intervention using the HRA, patient surveys, and qualitative feedback. Intervention patients received detailed feedback from the HRA and they were encouraged to discuss the HRA report at their next wellness visit in order to develop a personalized wellness plan.Results: Estimated life expectancy and its derivatives, including Real Age and Wellness Score were significantly impacted by the HRA implementation (P<0.001). The overall rate of 10 preventive maneuvers improved by 4.2% in the intervention group vs. control (P = 0.001). The HRA improved the patient-centeredness of care, measured by the CAHPS PCC-10 survey (P = 0.05). HRA use was strongly associated with better self-rated overall health (OR = 4.94; 95% CI, 3.85–6.36) and improved up-to-dateness for preventive services (OR = 1.22; 95% CI, 1.12–1.32). A generalized linear model suggested that increase in Wellness Score was associated with improvements in patient-centeredness of care, up-to-dateness for preventive services and being in the intervention group (all P<0.03). Patients were satisfied with their HRA-experience, found the HRA report relevant and motivating and thought that it increased their health awareness. Clinicians emphasized that the HRA tool helped them and their patients converge on high-impact, evidence-based preventive measures.Conclusions: Despite study limitations, results suggest that a comprehensive, web-based, and goal-directed HRA tool can improve the receipt of preventive services, patient-centeredness of care, behavioral health outcomes, and various wellness indicators in primary care settings.Citation: Nagykaldi ZJ, Voncken-Brewster V, Aspy CB, Mold JW. Novel Computerized Health Risk Appraisal May Improve Longitudinal Health and Wellness in Primary Care. Appl Clin Inf 2013; 4: 75–87http://dx.doi.org/10.4338/ACI-2012-10-RA-0048
Keywords: Health risk appraisal; health information technology; goal-directed care; prioritization; wellness